Perilaku Menyusui pada Ibu dengan HIV-AIDS di Kota Yogyakarta - Ghazali, Pariawan Lutfi; Maulida, Faizia (Media Kesehatan Masyarakat Indonesia, 2019)
The World Health Organization (WHO) recommends exclusive breastfeeding for 6 months for children born to HIV infected mothers who have received ARV therapy. This study aims to determine perceptions, behaviors, and factors that influence breastfeeding behavior in mothers with HIV-AIDS in Yogyakarta. This study use qualitative research method, with in-depth interviews and observation as data collection methods. Research subjects were breastfeeding mothers with HIV-AIDS, family, and chaperones. Data validity was tested by source triangulation method. Research data were processed using the fixed comparison method. This research shows that breastfeeding mothers with HIV-AIDS in Yogyakarta believes that the process of providing nutrition to infants is the nature of a woman that can not be replaced by anyone. The behavior of breastfeeding mothers with HIV-AIDS in Yogyakarta is divided into mothers who provide formula milk, breast milk, and donor breast milk. Factors that influence breastfeeding behavior of mothers with HIV-AIDS in Yogyakarta, namely internal factors and support from family, chaperones., health workers, and peers. This research concludes that breastfeeding mothers with HIV-AIDS have reasons related to the risk of HIV transmission in deciding breastfeeding behavior.